2018
DOI: 10.1055/s-0038-1660436
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism (VTE) Incidence and VTE-Associated Survival among Olmsted County Residents of Local Nursing Homes

Abstract: Nursing home (NH) residency is an independent risk factor for venous thromboembolism (VTE), but the VTE burden within the NH population is uncertain. This study estimates VTE incidence and VTE-associated mortality among NH residents. We identified all NH residents in any NH in Olmsted County, Minnesota, United States, 1 October 1998 to 31 December 2005 and all first lifetime VTE among county residents to estimate VTE incidence while resident of local NHs (NHVTE), using Centers for Medicare and Medicaid Service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The process for verification of VTE events in the REP has previously been described. 11,[13][14][15][16] Incident DVT events occurring in Olmsted County, Minnesota residents were objectively diagnosed by compression venous duplex ultrasonography, impedance plethysmography, computed tomographic venography, magnetic resonance imaging, venography, or pathology examination of thrombus removed at surgery or autopsy and were confirmed by study-trained registered nurses. PE within a segmental or larger artery was objectively diagnosed by a ventilation/perfusion lung scan interpreted as high probability for PE, computed tomographic pulmonary angiography, magnetic resonance imaging, pulmonary angiography, or pathology examination of thrombus at surgery or autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The process for verification of VTE events in the REP has previously been described. 11,[13][14][15][16] Incident DVT events occurring in Olmsted County, Minnesota residents were objectively diagnosed by compression venous duplex ultrasonography, impedance plethysmography, computed tomographic venography, magnetic resonance imaging, venography, or pathology examination of thrombus removed at surgery or autopsy and were confirmed by study-trained registered nurses. PE within a segmental or larger artery was objectively diagnosed by a ventilation/perfusion lung scan interpreted as high probability for PE, computed tomographic pulmonary angiography, magnetic resonance imaging, pulmonary angiography, or pathology examination of thrombus at surgery or autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…2 Some patients will be discharged to nursing home care, where VTE rates are up to 30fold higher than in the general population and highest in the initial 7 days of admission. 3 In the United States, approximately 200,000 VTE events occur annually following discharge. 4 There is currently a disconnect among guideline recommendations, clinical trial data, and clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Apenteng et al ’s prospective cohort study demonstrated that in the same population, the incidence of VTE was obviously higher in long-term bedridden people than in old people who were able to act on their own in care homes ( 17 ). Petterson et al showed that nursing home residents had a substantially increased risk and the highest VTE incidence within 7 days after admission ( 18 ). Several similar reports have supported this view ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%